Grip Force as a Measure of Stress in Psychomotor Mobile Tasks - Sahar, Yotam (2022 10th International Conference on Affective Computing and Intelligent Interaction Workshops and Demos (ACIIW), 2022)
Stress is one of the main factors that affect human performance. Measuring stress may help to continuously adapt training systems and operational systems to the state of the operator, but many physiological stress measures are intrusive and suffer from large delays, therefore not suitable for this end. This PhD project is focused on the establishment of grip force as a measure of stress, suitable for static as well as for mobile environments. Among the objectives of this research are the study of grip force characteristics, its proper measurement method in mobile environments and to investigate the usefulness of a grip force-based stress-adaptive training method.